2021
DOI: 10.1155/2021/5558449
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ensemble Learning Using Weight Voting Protocol in the Prediction of Pile Bearing Capacity

Abstract: Accurate prediction of pile bearing capacity is an important part of foundation engineering. Notably, the determination of pile bearing capacity through an in situ load test is costly and time-consuming. Therefore, this study focused on developing a machine learning algorithm, namely, Ensemble Learning (EL), using weight voting protocol of three base machine learning algorithms, gradient boosting (GB), random forest (RF), and classic linear regression (LR), to predict the bearing capacity of the pile. Data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The determination of foundation bearing capacity is crucial in the design of foundation. Therefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [ 25 34 ]. Through the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Field Bearing Capacity Model Test Of Special Water Conservan...mentioning
confidence: 99%
“…The determination of foundation bearing capacity is crucial in the design of foundation. Therefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [ 25 34 ]. Through the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Field Bearing Capacity Model Test Of Special Water Conservan...mentioning
confidence: 99%
“…As many trainers can be added as much as a better performance [111]. Weight voting was used in many works [113]- [115], [119]- [124]. The relative accuracy 𝑎𝑐𝑐 𝑐 (𝑡) of a trainer 𝑡 ∈ 𝑇 with respect to a class 𝑐 ∈ 𝐶 can be stated as the times that 𝑡 classified an element 𝑥 ∈ 𝐷 correctly as an element from the class 𝑐 divided by the total number of elements in the class 𝑐 𝑎𝑐𝑐 𝑐 (𝑡) = |𝑝𝑟𝑒 𝑡 (𝑥∈𝐷)=𝑐|…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that stacking models provided more satisfactory performance compared with single model. Pham and Vu (2021) developed an ensemble earning algorithm based on weight voting method using three individual classifier including GB, RF, and classic LR for prediction of pile bearing capacity. They confirmed that the ensemble method provided the best performance for the evaluation of pile capacity in terms of evaluation indicators including R 2 , RMSE, and MAE, namely mean absolute error.…”
Section: Introductionmentioning
confidence: 99%